Concentração, rivalidades e impactos sobre o risco no mercado bancário brasileiro - Bottrel, Mariana Araújo e Silva (2014)
It is essential that the financial intermediaries operate well in order to offer financial products to attend the society s needs efficiently, providing economic growth. Besides, a healthy banking system is extremely important for the solidity of the financial system of a country and the social welfare. Therefore, it is necessary to study the market structure, with their concentration rates and the possibility to exercise market power of the firms. Also, it is possible to relate the impacts of this market structure to the risks taken by the banks. In order to measure the concentration, it has been used the following techniques: (i) Herfindahl-Hirschman Index (HHI); (ii) Concentration Rates ( CR). To watch the possibility of market power exercising and rivalry, two methods were used: (i) unit root tests; and (ii) unit root tests with panel data. The results show that there has been a large increase in concentration, especially during the beginning of the global financial crisis in 2008. Moreover, it shows that there is possibility of effective rivalry. For the relationship between structure and risk, it has been used a model with panel data, according to Araújo e Jorge Neto (2007). The result was that the relationship between risk and concentration is positive. On conclusion, effective rivalry in the markets studied is possible, which reduces the possibility of the exercise of market power due to an increase in concentration. The concentration may also not have contributed to reduce the risks taken by banks. Keywords: Economic Measures. Econometrics. Commercial Bank. Financial Crisis.